2003
DOI: 10.1152/ajpheart.00396.2003
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic consequences of β1-tubulin expression and MAP4 decoration of microtubules in adult cardiocytes

Abstract: .-In pressure-overload cardiac hypertrophy, microtubule network densification is one cause of contractile dysfunction. Cardiac transcriptional upregulation of ␤ 1-tubulin rather than the constitutive ␤ 4-tubulin and of microtubuleassociated protein (MAP)4 accompanies hypertrophy, with extensive microtubule decoration by MAP4. Because MAP4 stabilizes microtubules, and because the isoform-variable carboxy terminus of ␤-tubulin binds to MAP4, we wished to determine whether one or both of these proteins has etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Adenoviral-mediated overexpression of these proteins in normal adult cardiac myocytes revealed that MAP4 is sufficient for these myocytes to develop microtubular structure similar to that observed in myocytes isolated from pressure-overloaded hearts. In contrast, adenoviralmediated expression of either ␤ 4 -or ␤ 1 -tubulin had no significant effect on microtubule assembly (864). The increased density of microtubules present within pressureoverloaded myocytes resulted in a significant increase in the viscous load placed on the myofilaments.…”
Section: Microtubulesmentioning
confidence: 86%
“…Adenoviral-mediated overexpression of these proteins in normal adult cardiac myocytes revealed that MAP4 is sufficient for these myocytes to develop microtubular structure similar to that observed in myocytes isolated from pressure-overloaded hearts. In contrast, adenoviralmediated expression of either ␤ 4 -or ␤ 1 -tubulin had no significant effect on microtubule assembly (864). The increased density of microtubules present within pressureoverloaded myocytes resulted in a significant increase in the viscous load placed on the myofilaments.…”
Section: Microtubulesmentioning
confidence: 86%
“…Myocardial protein fractions were prepared as before (50). For the total tubulin fraction, the myocardium was homogenized in 1% SDS buffer containing (in mM) 10 Tris·HCl (pH 7.4), 0.5 DTT, and 1 Na 3VO4, boiled for 5 min, and centrifuged at 16,000 g, 4°C for 10 min; this supernatant was saved as the total protein fraction.…”
Section: Methodsmentioning
confidence: 99%
“…The most definitive solution, however, would be to close the loop and address the microtubule hypothesis directly in a context apart from hemodynamic alterations in vivo or microtubule alterations in vitro. On the basis of some of our other work defining the basic causes of microtubule network densification in cardiac hypertrophy (21,23,28), I very recently tested, via a collaboration with F. Cabral and D. R. Menick, the effects of ␤ 1 -tubulin mutants that had been selected for their effects on microtubule stability and then expressed in the hearts of transgenic mice (4). We found that when intrinsic microtubule stability was increased as an isolated variable, the contractile defects characteristic of pressure-overloaded hypertrophied myocardium were reproduced.…”
Section: Is There a Specific Link Between Microtubule Network Densitymentioning
confidence: 99%
“…Instead, active transport is required for this purpose, and microtubules supply this function: the dynein family of motor proteins moves these cargoes along microtubules toward the cell center, and the kinesin family of motor proteins moves these cargoes along microtubules from the nuclei toward the cell periphery. In cardiac hypertrophy, the microtubules not only proliferate but also become heavily decorated by microtubule-associated protein-4, the predominant cardiac microtubule-associated protein (23,28). One consequence of this is that the normal microtubule transport function is sterically inhibited by the presence of microtubule-associated protein-4 on these transport tracks, and as one example that may help explain ␤-adrenergic receptor downregulation in cardiac hypertrophy and failure, we have shown that activated G proteincoupled receptors fail to be recycled properly to the cell membrane (2,3).…”
Section: Future Directionsmentioning
confidence: 99%